An Analysis of Differences Between “Communication” and “Expression” in Art: From Cave to Modern Art - Budiarta, I Dewa Putu Gede; Mustika, I Ketut; Sastrawan, Dewa Ayu Eka Savitri (Abjad Journal of Humanities & Education, 2025)
Communicating is a human activity in stating one thing with an agreed way of doing it between the one who sends it and the one who receives it, make that in language, signs, or symbols. Expression is an effort in expressing an idea, either in language, signs or symbols, without any agreement from the sender and the receiver. Communication and expression in painting has become something that just happens, since art was created when human knowledge knows how to write up to writing is no longer needed as pressing buttons would finish the job. In communicating through an artwork there is an effort so that the target understands the idea being stated, while expression is purely expressing an idea without others consent in understanding it. Hence this analysis aims to dissect the differences through several artworks that have existed in the visual arts: from cave to modern art. This analysis also aims to provide extended knowledge on analyzing works of art through the ages.